Exostoma tibetana, a new glyptosternine catfish from the lower Yarlung Tsangpo River drainage in southeastern Tibet, China (Siluriformes: Sisoridae) - Gong, Zheng; Lin, Pengcheng; Liu, Fei; Liu, Huanzhang (Zootaxa, 2018)
Exostoma tibetana, new species, is described from the lower Yarlung Tsangpo River drainage in southeastern Tibet, China. It is distinguished from congeners by having an adipose fin separate from the upper procurrent caudal-fin rays and incised at the posterior extremity of its base; the tip of the pelvic fin not reaching to the anus when adpressed; 10 branched pectoral-fin rays; and morphometric features associated with the body depth, adipose-fin base length, caudal-peduncle depth, snout length, and eye diameter. The validity of this new species was also supported by molecular phylogenetic analysis based on Cyt b gene sequences.